A geomorphological assessment of wash-load sediment fluxes and floodplain sediment sinks along the lower Amazon River - Park, Edward (2019)
We present the first spatiotemporal surface suspended sediment concentration (SSSC) analysis of the lower Amazon River, by combining geomorphological mapping, hydrosedimentological field investigations, and 15 years (2001–2015) of weekly averaged wash-load (fine sediment) fluxes at gauging stations estimated from field-calibrated remote-sensing models of SSSC. We found a downstream increase in the magnitude of sediment sinks, where the floodplain geomorphic style controls sediment trapping, and we conclude that the sediment net loss in the floodplain happens during the rising phase through seasonal hydrosedimentological connectivity. On average, 120 million tons per year of fine sediments are accumulated in the floodplain along 765 km of the lower Amazon River (from the confluence with the Madeira River to Monte Alegre city), making the lower Amazon River one of the most important fluvial sediment sinks among the world’s axial rivers.